Plaque Control with Newer Dimension in Children - Harshita Singh (Institute of Medico-legal Publications Pvt Ltd, 2020)
Plaque management is the routine removal of dental plaque, oral biofilm and also the avoidance of itsaccumulation on the teeth surface and other adjacent parts of the oral cavity. Occurrence of the commongingival and the periodontal diseases in the oral cavity is due to the presence of dental plaque which isthe utmost primary etiological factor related to this. Dental caries along with periodontal disease are themajor diseases that start very early during childhood and which should be stopped before the gradual onsetof the disease. Dental plaque management using distinct approaches and agents benefit track the onsetof periodontal diseases. An aggregation of multiple oral hygiene edification and mechanical skilled teethbrushing at regular time intervals will avoid the progression of dental caries and periodontal diseases almostentirely. Hereby, this article provides an overview of mechanical plaque control approaches with certainchanges to include children and adolescents for successful dental plaque management.